The labor of the mind : intellect and gender in Enlightenment cultures - LaVopa, Anthony J., 1945- (Intellectual history of the modern age., 2017)
The Labor of the Mind plumbs the Enlightenment's social and cultural logic of conceiving the mind as manly; considers the textual representations of the manly mind; and examines the ways in which it was subverted or at least subtly questioned.